Injectable Hydrogel Based on Protein-Polyester Microporous Network as an Implantable Niche for Active Cell Recruitment - V.H. Giang Phan; Mohanapriya Murugesan; Panchanathan Manivasagan; Thanh Loc Nguyen; Thuy-Hien Phan; Cuong Hung Luu; Duy-Khiet Ho; Yi Li; Jaeyun Kim; Doo Sung Lee; Thavasyappan Thambi (MDPI AG, 2022)
Despite the potential of hydrogel-based localized cancer therapies, their efficacy can be limited by cancer recurrence. Therefore, it is of great significance to develop a hydrogel system that can provoke robust and durable immune response in the human body. This study has developed an injectable protein-polymer-based porous hydrogel network composed of lysozyme and poly(ε-caprolactone-co-lactide)-b-poly(ethylene glycol)-b-poly(ε-caprolactone-co-lactide (PCLA) (Lys-PCLA) bioconjugate for the active recruitment dendritic cells (DCs). The Lys-PCLA bioconjugates are prepared using thiol-ene reaction between thiolated lysozyme (Lys-SH) and acrylated PCLA (PCLA-Ac). The free-flowing Lys-PCLA bioconjugate sols at low temperature transformed to immovable gel at the physiological condition and exhibited stability upon dilution with buffers. According to the in vitro toxicity test, the Lys-PCLA bioconjugate and PCLA copolymer were non-toxic to RAW 263.7 cells at higher concentrations (1000 µg/mL). In addition, subcutaneous administration of Lys-PCLA bioconjugate sols formed stable hydrogel depot instantly, which suggested the in situ gel forming ability of the bioconjugate. Moreover, the Lys-PCLA bioconjugate hydrogel depot formed at the interface between subcutaneous tissue and dermis layers allowed the active migration and recruitment of DCs. As suggested by these results, the in-situ forming injectable Lys-PCLA bioconjugate hydrogel depot may serve as an implantable immune niche for the recruitment and modification of DCs.